“Green Writing”, “Green Reading”: Ecological humanities as a literary research project - Tomaszewska, Wiesława (Studia Ecologiae et Bioethicae, 2018)
The article discusses one of the new methodologies in literary studies i.e. ecological humanities. Referring to theoretical texts, the author critically examines their main ideas. In this spirit, she comments on the interpretation of literary works based on the methodology offered by bio-humanities, focusing on the sketch on the novel “On the Rocks of Calvados” (1884) by Antoni Sygietynski. Author presents “green writing” as common practice among authors of literary works and puts forward a hypothesis that literature might be ascribed with a precursory attribute in the field of ecology.